Effect of 3-methacryloxypropyltrimethoxysilane on diametral tensile strength of rice husk silica-based dental composite - Febrida, Renny; Wulanhapsari, Madeiva; Faza, Yanwar; Karlina, Elin; Cahyanto, Arief; Solihudin, Solihudin; Eddy, Diana Rakhmawati (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Rice husk silica has been studied as a filler in dental composite, however, the mechanical properties of the resulting composites are below the commercial due to the poor surface modification between silica and resin matrix. 3-methacryloxyprpyltrimethoxysilane (MPTS) is one of the coupling agents that are effective to modify the silica surface. The purpose of this study to analyze the effect of MPTS on the diametral tensile strength (DTS) of the self-made composite using rice husk silica. Methods: The research type of this study was an experimental research laboratory. The samples (26 samples) were divided into two groups, namely the test group (using MPTS-modified silica) and the control group (using non-modified silica). The samples were cylindrical in shape with a diameter of 6.0 ± 0.1 mm and a height of 3.0 ± 0.1 mm according to ANSI/ADAS No. 27, 1993 and ISO 4049, 1988. The Fourier Transform Infrared (FTIR), HORIBA, was used to characterize the MPTS grafting on the silica surface. The DTS value is measured by Universal Testing Machine (UTM), Lloyd LRX Plus. Results: FTIR presents the additional peak of carboxyl and methacryloyl group at 1716, 1555, and 1410 cm-1 wavenumber, respectively in MPTS-modified silica. The DTS value of the test group was 43.40 ± 4.43 MPa and the control group was 25.80 ± 2.63 MPa. The test group was significantly higher than the control group (p-value = 0.001). Conclusion: The MPTS is effective to enhance the DTS value of rice husk silica-based composite.Keywords: Rice husk silica; dental composite; diametral tensile strength; 3-methacryloxypropyltrimethoxysilane.